2013
DOI: 10.1111/papr.12131
|View full text |Cite
|
Sign up to set email alerts
|

Kyphoplasty Increases Vertebral Height, Decreases Both Pain Score and Opiate Requirements While Improving Functional Status

Abstract: Vertebral compression fractures can result from advanced osteoporosis, or less commonly from metastatic or traumatic insults to the vertebral column, and result in disabling pain and decreased functional capacity. Various vertebral augmentation options including kyphoplasty aim at preventing the sequelae of pain and immobility that can develop as the result of the vertebral fractures. The mechanism for pain relief following kyphoplasty is not entirely understood, and the restoration of a portion of the lost ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…It was determined that the procedure increases vertebral height by nearly 42% and improves function while decreasing pain and the need for opioid analgesics. 68 Similar results were also obtained by Zarate et al, who observed a reduction in pain for the full 2-year follow-up. 69 A substantial amount of literature compares the two original vertebral augmentation procedures, vertebroplasty and kyphoplasty.…”
Section: Kyphoplastysupporting
confidence: 80%
“…It was determined that the procedure increases vertebral height by nearly 42% and improves function while decreasing pain and the need for opioid analgesics. 68 Similar results were also obtained by Zarate et al, who observed a reduction in pain for the full 2-year follow-up. 69 A substantial amount of literature compares the two original vertebral augmentation procedures, vertebroplasty and kyphoplasty.…”
Section: Kyphoplastysupporting
confidence: 80%
“…Many studies have shown the effectiveness of kyphoplasty in restoring vertebral height and relieving pain. [4][5][6]8] Kyphoplasty involves placing a balloon into the vertebral body and creating a void within that body that can then be filled cement injected under lower pressures, to reduce the risk of cement leakage. [7] Here, we uniquely correlated cement volumes injected with pain, disability, and quality of life indices in those undergoing percutaneous kyphoplasty for the treatment of vertebral compression fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, previous opioid consumers were able to decrease their opioid consumption by 48%, which was VWDWLVWLFDOO\ VLJQL¿FDQW 2XU UHVXOWV DUH LQ FRQJUXLW\ ZLWK WKH ¿QGLQJV RI RWKHU VLPLODU studies. 22,24 Our analysis also showed that neither gender nor vertebral level (thoracic vs. OXPEDU KDG DQ\ LQÀXHQFH RQ RXU PHDVXUHG outcomes.…”
Section: Discussionmentioning
confidence: 67%